Fingering instability of a suspension film spreading on a spinning disk - Kulkarni, Mayuresh; Sahoo, Subhadarshinee; Doshi, Pankaj; Orpe, Ashish V. (Physics of Fluids, 2016)
The spreading of a thin film of suspension on a spinning disk and the accompanying contact line instability is studied through flow visualization experiments. The critical radius for the onset of instability shows an increase with increase in the particle fraction (phi(p)) before decreasing slightly at the highest value of phi(p) studied, while the instability wavelength (lambda) exhibits a non-monotonic dependence. The value of lambda is close to that for a partially wetting liquid at lower phi(p), it decreases with increasing phi(p) to a minimum before increasing again at largest phi(p). The non-monotonic trends observed for lambda are discussed in light of the linear stability analysis of thin film equations derived for suspensions by Cook et al. [''Linear stability of particle-laden thin films,'' Eur. Phys. J.: Spec. Top. 166, 77 (2009)] and Balmforth et al. [''Surface tension driven fingering of a viscoplastic film,'' J. Non Newtonian Fluid Mech. 142, 143 (2007)]. Published by AIP Publishing.